A polycarbonate composition with low shrinkage, preparation method and application thereof
By using composite sheet fillers and spherical fillers in polycarbonate resin, combining dimensional effect and rolling effect, the problems of high shrinkage and low weld line strength of polycarbonate materials are solved, and a polycarbonate composition with low shrinkage, excellent rigidity and toughness are achieved, which is suitable for precision injection molding and the production of complex mechanical parts.
Patent Information
- Application Number
- CN202311089625.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-08-28
AI Technical Summary
The shrinkage rate of polycarbonate materials is still relatively high, and they cannot have good rigidity and toughness at the same time. The welding wire strength of the parts is low, making it difficult to meet the application needs of precision injection molding and complex mechanical parts.
By adding composite sheet filler and spherical filler to the polycarbonate resin, the size and rolling effects of sheet filler and spherical filler of different average particle sizes are used to form good riveting and dispersion, reducing shrinkage and improving rigidity and toughness.
The polycarbonate composition has achieved low shrinkage, excellent rigidity and toughness, and the welding wire of the parts is high and has a good appearance, which meets the quality requirements of various processing technologies and post-assembly.
Smart Images

Figure BDA0004417260490000021 
Figure BDA0004417260490000031 
Figure BDA0004417260490000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of engineering plastics, and more specifically to a polycarbonate composition with low shrinkage, a preparation method and application thereof. Background Art
[0002] Polycarbonate material, a material with polycarbonate as the main component. Polycarbonate is an amorphous polymer that becomes a transparent glass-like substance after melting and cooling, and has excellent optical and mechanical properties. Polycarbonate material has a high melting point, is also resistant to low temperatures, has low water absorption, has good impact resistance, insulation and aging resistance, and can withstand inorganic and organic dilute acids.
[0003] With the trend of replacing steel with plastic, the application fields of plastics are becoming more and more extensive, so people's requirements for the dimensional accuracy of plastic parts are becoming increasingly stringent. Precision injection molding has become an important method of plastic molding, which is characterized by high precision of injection molded parts, including dimensional accuracy and repeatability. In order to meet the requirements of precision injection molding, it is necessary to develop polycarbonate materials with a low shrinkage rate (<0.3%). In addition, for important components in computers, video recorders, electronic display screens and color TVs, as well as application scenarios such as mechanical equipment housings, covers and frames, polycarbonate materials are also required to have excellent rigidity and toughness.
[0004] The Chinese patent named Aromatic Polycarbonate Resin Composition reduces the shrinkage of the material by adding hollow microspheres to the aromatic polycarbonate resin, but its shrinkage can only reach 0.4-0.6%, which is still a relatively high level; in addition, due to the low strength of the one-dimensional hollow microspheres at the bonding line, the screw columns of the parts made of this material are prone to cracking, which in turn leads to low weld line strength, making it difficult to meet related application scenarios.
[0005] Therefore, it is necessary to solve the problems that the shrinkage rate of the current polycarbonate material is still relatively high, it cannot have good rigidity and toughness at the same time, and the weld line strength of the product is low. Summary of the invention
[0006] The primary purpose of the present invention is to overcome the above-mentioned problems that the shrinkage rate of the current polycarbonate material is still relatively high, it cannot have good rigidity and toughness at the same time, and the weld line strength of the product is low, and to provide a polycarbonate composition with low shrinkage rate. The polycarbonate composition has low shrinkage rate, excellent rigidity and toughness, and the weld line strength of the product is high and the appearance is good, which can meet the quality requirements of various processing techniques and post-assembly.
[0007] A further object of the present invention is to provide a method for preparing the polycarbonate composition.
[0008] A further object of the present invention is to provide use of the polycarbonate composition in preparing a display screen, a housing or a cover.
[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0010] A polycarbonate composition with low shrinkage, comprising the following components in parts by weight:
[0011]
[0012] The composite sheet filler is obtained by compounding the first sheet filler and the second sheet filler in a mass ratio of 1:(0.33-3), the average particle size of the first sheet filler is 5-7 μm, and the average particle size of the second sheet filler is 0.5-2 μm. The average particle size of the first sheet filler can be 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, etc.; the average particle size of the second sheet filler can be 0.5 μm, 1 μm, 1.5 μm, 2 μm, etc. As well as the specific point values between the above point values, the present invention will no longer exhaustively list the specific point values included in the range due to space limitations and for the sake of simplicity.
[0013] The inventor of the present invention has found through many studies that the polycarbonate composition obtained by adding spherical fillers and composite flaky fillers compounded with a specific average particle size and mass ratio to polycarbonate resin has low shrinkage and excellent rigidity and toughness. The reason is: on the one hand, compounding two flaky fillers with different average particle sizes can increase the contact area between the matrix resin and the flaky filler through the size effect, forming a good riveting, so that the shrinkage of the polycarbonate composition is reduced to a certain extent, and on this basis, the spherical filler is added, and the rolling effect of the spherical filler can disturb the orientation of the flaky filler, so that the size effect is further amplified, so that the polycarbonate composition flows more smoothly during injection molding, and the shrinkage is further reduced (<0.3%), thereby making the polycarbonate composition product have good dimensional stability; on the other hand, the size effect brought by the flaky fillers with two different average particle sizes can produce a synergistic effect with the spherical filler, so that the filler has good dispersibility, thereby achieving a balance between the rigidity and toughness of the polycarbonate composition, and having excellent rigidity and toughness. In addition, the combination of the composite flake filler and the spherical filler can also make the weld line strength of the polycarbonate composition product high (high clamping force of the metal screw column) and good appearance.
[0014] That is, the polycarbonate composition of the present invention has low shrinkage, excellent rigidity and toughness, and the weld line strength of the product is high and the appearance is good, and can meet the quality requirements of various processing techniques and post-assembly.
[0015] Preferably, the polycarbonate composition comprises the following components in parts by weight:
[0016]
[0017]
[0018] The polycarbonate resin, toughening agent and spherical filler commonly used in the art can be used in the present invention.
[0019] Optionally, the polycarbonate resin is at least one of an aromatic polycarbonate resin or an aliphatic polycarbonate resin.
[0020] Optionally, the weight average molecular weight of the polycarbonate resin is 22,000 to 30,000.
[0021] The weight average molecular weight of the polycarbonate resin of the present invention can be measured by gel chromatography.
[0022] Preferably, the weight average molecular weight of the polycarbonate resin is 24,500 to 30,000.
[0023] Under the condition of the weight average molecular weight, the obtained polycarbonate composition has a higher clamping force of the metal screw column while maintaining good rigidity and toughness and low shrinkage, so that the weld line strength of the product is higher and the appearance is better.
[0024] Preferably, the toughening agent is an ethylene copolymer toughening agent, including but not limited to EMA, EBA, EVA and the like.
[0025] More preferably, the toughening agent is ethylene-butyl acrylate copolymer (EBA).
[0026] By selecting ethylene-butyl acrylate copolymer as a toughening agent, the obtained polycarbonate composition has better toughness, lower shrinkage rate and higher clamping force of metal screw column.
[0027] Preferably, the mass ratio of the spherical filler to the composite flaky filler is 1:(15-50).
[0028] Optionally, the average particle size of the spherical filler is 0.2 to 45 μm, preferably 0.22 to 7.5 μm.
[0029] The average particle size of the spherical filler can be 0.2μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0030] Optionally, the spherical filler is at least one of glass microspheres, titanium dioxide or calcium carbonate.
[0031] Preferably, the first flaky filler is at least one of talc, flaky kaolin, montmorillonite, mica or flake glass powder, and the second flaky filler is at least one of talc, flaky kaolin, montmorillonite, mica or flake glass powder.
[0032] The first plate-like filler and the second plate-like filler may have the same or different components.
[0033] More preferably, the first plate-like filler is talcum powder, and the second plate-like filler is talcum powder.
[0034] Preferably, the polycarbonate composition further comprises 1 to 30 parts of a flame retardant, more preferably 8 to 14 parts.
[0035] Preferably, the polycarbonate composition further comprises 0.01 to 5 parts of an anti-drip agent, and more preferably 0.3 to 1 part.
[0036] In order to meet more application scenarios, when the present invention adds a flame retardant and an anti-drip agent, the polycarbonate composition of the present invention has a low shrinkage rate, excellent rigidity and toughness, and a high weld line strength of the product. It also has good initial thin-wall flame retardancy (1.0mm V-0), and after double 85 wet heat aging treatment, it still has good thin-wall flame retardancy (1.0mm V-0). Among them, for the initial flame retardancy, the flammability test is carried out in accordance with the "Flammability Test of Plastic Materials, UL94-2022" regulations. The flame retardant grade is derived based on the burning rate, extinguishing time, ability to resist falling, and whether the falling is burning. Samples used for testing: 125mm length and 13mm width. The thickness of the present invention is selected as 1.0mm when testing. According to the UL94 regulations, the flame retardant grade of the material can be classified into (UL94-HB): V0, V1, V2, 5VA and 5VB. For the flame retardancy after damp heat aging, the samples were first subjected to damp heat aging treatment for 500 h in a constant temperature and humidity chamber with a temperature set at 85°C and a humidity of 85%, and then a flammability test was performed according to the procedure of "Flammability Test of Plastic Materials, UL94-2022".
[0037] The present invention has no particular limitation on the flame retardant. Optionally, the flame retardant is at least one of bisphenol A bis(diphenyl phosphate), triphenyl phosphate or resorcinol-bis(bisbisphosphate).
[0038] The present invention has no special restrictions on the anti-dripping agent. Optionally, the anti-dripping agent is at least one of PTFE, PTFE / SAN blend, PTFE / PE blend or PTFE / ABS blend. Preferably, the polycarbonate composition further comprises 0.1 to 2 parts of other additives.
[0039] More preferably, the other auxiliary agent is at least one of an antioxidant or a lubricant.
[0040] Optionally, the antioxidant is at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, phosphite or n-octadecanol β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
[0041] Optionally, the lubricant is at least one of polyol ester, polyethylene wax or montan wax.
[0042] The method for preparing the polycarbonate composition comprises the following steps:
[0043] The components are mixed, melt-extruded and pelletized to obtain the polycarbonate composition.
[0044] Preferably, the preparation method comprises the following steps: stirring and mixing the components in a high-speed mixer, and then melt-extruding and granulating the components in a twin-screw extruder to obtain the polycarbonate composition.
[0045] More preferably, the stirring speed is 50 to 200 rpm; the aspect ratio of the twin-screw extruder is 36 to 60:1, the barrel temperature is 230 to 290° C., and the screw speed is 200 to 800 rpm.
[0046] The use of the polycarbonate composition in preparing display screens, housings or covers also falls within the protection scope of the present invention.
[0047] Optionally, the screen display is a computer screen, a video recorder display or a color television display.
[0048] Optionally, the housing is a mechanical equipment housing.
[0049] Optionally, the cover is a mechanical equipment cover.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] The polycarbonate composition of the invention has low shrinkage, excellent rigidity and toughness, and the weld line strength of the manufactured part is high and the appearance is good, and can meet the quality requirements of various processing techniques and post-assembly. DETAILED DESCRIPTION
[0052] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0053] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0054] Polycarbonate 1#: PC 1300-10NP, LG, South Korea, weight average molecular weight 24500;
[0055] Polycarbonate 2#: PC 1300-03NP, LG, South Korea, weight average molecular weight 30000;
[0056] Polycarbonate 3#: PC 1300-22NP, LG, South Korea, weight average molecular weight 22000;
[0057] Flame retardant: bisphenol A bis(diphenyl phosphate), commercially available;
[0058] Anti-dripping agent: PTFE / SAN blend, commercially available;
[0059] Other additives: antioxidant 1076, commercially available;
[0060] Toughener 1#: Elvaloy-AC1125, DOW, EMA (ethylene-methyl acrylate copolymer);
[0061] Toughener 2#: Elvaloy PTW, DuPont, EBA (ethylene-butyl acrylate copolymer);
[0062] Toughening agent 3#: Evaflex EVA460, Mitsui DuPont, EVA (ethylene-vinyl acetate copolymer);
[0063] Toughening agent 4#: ABS POW HR181, Kumho, high rubber powder;
[0064] Spherical filler 1#: titanium dioxide, Chemours R-103, average particle size 0.22 μm;
[0065] Spherical filler 2#: titanium dioxide, TR50 2000 mesh, Guangdong Yuanlei Powder Co., Ltd., average particle size 6.5 μm;
[0066] Spherical filler 3#: titanium dioxide, TR50 300 mesh, Guangdong Yuanlei Powder Co., Ltd., average particle size 45 μm;
[0067] Spherical filler 4#: calcium carbonate, Filmlink 520, IMERYS, average particle size 2.7 μm;
[0068] The first flake filler 1#: talcum powder, BHS-1250A, Xufeng, Haicheng, Liaoning; average particle size 6.5-7 microns;
[0069] The first flake filler 2#: talcum powder, TYT-777, Liaoning Beihai Company, average particle size 5 microns;
[0070] The second flake filler 1#: talcum powder, HTP Ultra 5L, Liaoning Aihai, average particle size 0.5 μm;
[0071] The second flake filler 2#: talcum powder, HTP1, IMIFABI, average particle size 1.9 μm;
[0072] The filler involved in the present invention can be directly purchased from the market to obtain spherical fillers and flaky fillers of corresponding particle sizes, or can be purchased from the market and then sieved or ground according to the existing technology to obtain spherical fillers and flaky fillers of corresponding particle sizes.
[0073] Composite flake fillers 1 to 8#: homemade, with compositions as shown in Table 1; the preparation process is as follows: the first flake filler and the second flake filler are mixed to obtain.
[0074] Table 1 Formula of composite flake filler (parts by weight)
[0075]
[0076] Unless otherwise specified, the components (such as auxiliary agents) selected in the parallel examples and comparative examples are all the same commercially available products.
[0077] The performance of the polycarbonate compositions provided in the embodiments and comparative examples of the present invention was measured according to the following test methods:
[0078] Flexural modulus: According to the ASTM D790-2018 standard, the 3.0 mm flexural modulus was tested. After conditioning at room temperature of 25°C and humidity of 50% for more than 48 hours, 5 pieces were tested and the average value was taken as the final result.
[0079] Bending toughness: characterized by deflection, which is the linear displacement of the rod axis in the direction perpendicular to the axis or the linear displacement of the mid-plane of the plate and shell in the direction perpendicular to the mid-plane when subjected to force. According to the ASTMD790-2018 standard, a 3.2mm bending test is carried out, and the linear displacement of 5 rods is tested after conditioning at room temperature of 25℃ and humidity of 50% for more than 48 hours, and the average value is calculated. The average value is the final result; the larger the value, the greater the deflection and the better the bending toughness; the smaller the value, the smaller the deflection and the worse the bending toughness.
[0080] Shrinkage rate: The injection temperature is fixed at 265°C, the injection pressure is 50%, the injection speed is 50%, and a 2.0 mm cross shrinkage rate plate is injected. After injection, it is placed at room temperature of 25°C and humidity of 50% for conditioning for more than 48 hours, and then measured and recorded by the secondary element to obtain the shrinkage rate.
[0081] Metal screw column bonding strength: Measure the clamping force (N) required to tighten (lock) the screw until it slips or breaks according to GB / T 3098.9-2020 standard. Judge by the value of the maximum clamping force (N) of the screw column. The lower the value, the poorer the bonding, and the higher the value, the better the bonding.
[0082] The preparation process of the polycarbonate composition of each embodiment and comparative example of the present invention is as follows: weigh each component according to the ratio, add it into a high-speed mixer, stir and blend it, obtain a premix, and then extrude it in a twin-screw extruder, and obtain the polycarbonate composition after the melt granulation process. The stirring speed is 150 rpm; the aspect ratio of the twin-screw extruder is 40:1, the barrel temperature is 230-290°C, and the screw speed is 600 rpm.
[0083] Examples 1 to 19
[0084] Examples 1 to 19 provide a series of polycarbonate compositions, whose formulations are shown in Table 2, Table 3 and Table 4.
[0085] Table 2 Formulas of Examples 1 to 6 (parts by weight)
[0086]
[0087] Table 3 Formulas of Examples 7 to 14 (parts by weight)
[0088]
[0089]
[0090] Table 4 Formulas of Examples 15 to 19 (parts by weight)
[0091]
[0092]
[0093] Comparative Example 1
[0094] This comparative example provides a polycarbonate composition, the formula of which is different from that of Example 1 in that composite flake filler 1# is replaced by composite flake filler 7#.
[0095] Comparative Example 2
[0096] This comparative example provides a polycarbonate composition, the formula of which is different from that of Example 1 in that the composite flake filler 1# is replaced by a composite flake filler 8#.
[0097] Comparative Example 3
[0098] This comparative example provides a polycarbonate composition, the formulation of which is different from that of Example 1 in that the composite flake filler is entirely composed of the first flake filler 1#.
[0099] Comparative Example 4
[0100] This comparative example provides a polycarbonate composition, the formulation of which is different from that of Example 1 in that the composite flake filler is entirely composed of the second flake filler 1#.
[0101] Comparative Example 5
[0102] This comparative example provides a polycarbonate composition, the formula of which is different from that of Example 1 in that the composite flake filler 1# is replaced with the same weight portion of spherical filler 1#, that is, the composite flake filler 1# is not added, and the amount of spherical filler 1# added is 16 parts by weight.
[0103] Comparative Example 6
[0104] This comparative example provides a polycarbonate composition, the formula of which is different from that of Example 1 in that the spherical filler 1# is replaced with the same weight portion of the composite flake filler 1#, that is, the spherical filler 1# is not added, and the amount of the composite flake filler 1# added is 16 parts by weight.
[0105] The properties of the polycarbonate compositions of the embodiments and comparative examples were tested according to the above-mentioned test methods. The test results are shown in Table 5.
[0106] Table 5 Performance test results of the polycarbonate compositions of various embodiments and comparative examples
[0107]
[0108]
[0109] As can be seen from Table 5, the polycarbonate compositions of Examples 1 to 19 have a flexural modulus of more than 2900 MPa, a bending toughness of more than 15 mm, a shrinkage rate of less than 0.3%, and a metal screw column clamping force of more than 3800 N, indicating that the polycarbonate composition of the present invention has excellent rigidity and toughness, low shrinkage rate, and the weld line strength of the product is high and the appearance is good, which can meet the quality requirements of various processing techniques and post-assembly.
[0110] The mass ratio of the composite sheet filler added in Comparative Example 1 and Comparative Example 2 is not appropriate, wherein the shrinkage rate of the polycarbonate composition in Comparative Example 1 is 0.3%, and the clamping force of the metal screw column is too small; the clamping force of the metal screw column in Comparative Example 2 is also too small. The composite sheet filler selected in Comparative Example 3 is composed entirely of the first sheet filler, the shrinkage rate of the polycarbonate composition is too high, the toughness is too low, and the clamping force of the metal screw column is too small; the composite sheet filler selected in Comparative Example 4 is composed entirely of the second sheet filler, the shrinkage rate of the polycarbonate composition is too high, and the clamping force of the metal screw column is too small; Comparative Example 5 does not add the composite sheet filler, the rigidity of the polycarbonate composition is too low, and the shrinkage rate is too high; Comparative Example 6 does not add the spherical filler, the toughness of the polycarbonate composition is too low, the shrinkage rate is too high, and the clamping force of the metal screw column is too small.
[0111] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A polycarbonate composition with low shrinkage, characterized in that: The composition comprises the following components in parts by weight: The composite flaky filler is obtained by compounding a first flaky filler and a second flaky filler in a mass ratio of 1:(0.33-3), wherein the average particle size of the first flaky filler is 5-7 μm, and the average particle size of the second flaky filler is 0.5-2 μm; The spherical filler is at least one of glass microbeads, titanium dioxide or calcium carbonate; the first flake filler is talcum powder, and the second flake filler is talcum powder.
2. The polycarbonate composition according to claim 1, characterized in that: The polycarbonate composition comprises the following components in parts by weight:
3. The polycarbonate composition according to claim 1, characterized in that: The weight average molecular weight of the polycarbonate resin is 22,000 to 34,000.
4. The polycarbonate composition according to claim 1, characterized in that: The toughening agent is an ethylene copolymer toughening agent.
5. The polycarbonate composition according to claim 1, characterized in that: The mass ratio of the spherical filler to the composite flake filler is 1:(15-50).
6. The polycarbonate composition according to claim 1, characterized in that: The average particle size of the spherical filler is 0.2-45 μm.
7. The polycarbonate composition according to claim 1, characterized in that: The polycarbonate composition further comprises 1 to 30 parts of a flame retardant and 0.01 to 5 parts of an anti-dripping agent.
8. The method for preparing the polycarbonate composition according to any one of claims 1 to 7, characterized in that: The steps include: The components are mixed, melt-extruded and pelletized to obtain the polycarbonate composition.
9. Use of the polycarbonate composition according to any one of claims 1 to 7 in the preparation of display screens, housings or covers.
Citation Information
Patent Citations
High-thermal-conductivity two-component polyurethane structure adhesive as well as preparation method and application thereof
CN114133910A
Full-biodegradable film with high heat sealing strength as well as preparation method and application of full-biodegradable film
CN114921069A